Efficacy and safety of dual pathway inhibition in patients with cardiovascular disease. (14th October 2021) - Galli, M; Capodanno, D; D'Amario, D; Andreotti, F; Crea, F; Angiolillo, D J
Abstract: Background: The use of low dose of direct oral anticoagulants (DOAC) in adjunct to antiplatelet therapy, known as dual pathway inhibition (DPI), has been tested as an antithrombotic treatment regimen for the prevention of ischemic events in patients with cardiovascular disease (CVD). Purpose: The aim of this systematic review and meta-analysis is to determine the overall safety and efficacy of a DPI strategy in patients with CVD. Methods: Randomized controlled trials (RCTs) comparing the use of a DOAC at a low dose (LD) regimen, defined as a dosage below that approved for stroke prevention, versus placebo among patients with CVD treated with single or dual antiplatelet therapy were included. Incidence Rate Ratios (IRRs) with 95% confidence Intervals (CIs) were used to overcome different follow-up durations among the included trials. The primary efficacy endpoint was major adverse cardiovascular events (MACE) and the primary safety endpoint was major bleeding. A pre- specified subgroup analysis was performed according to the different low dose DOAC regimens used in the DPI arm [LD versus very low dose (VLD)]. Number needed to treat (NNT) and number needed to harm (NNH) were also calculated. Results: A total of 55, 782 patients from 7 RCTs were included. Compared with placebo, a DPI strategy was associated with a significant reduction in MACE (IRR 0.85, 95% CI 0.78–0.91; NNT 86) and a significant increase of major bleeding (IRR 2.05, 95% CI 1.50–2.80; NNH 89). Moreover, there was a significant reduction of myocardial infarction (IRR 0.86, 95% CI 0.78–0.97; NNT 355) and a significant increase of all bleeding (IRR 1.82, 95% CI 1.49–2.22; NNH 23) with DPI compared to placebo. There were no differences between groups for the outcomes of CV death (IRR 0.90, 95% CI 0.79–1.03; NNT 784), intracranial hemorrhage (IRR 1.18, 95% CI 0.71–1.96; NNH 1810) and fatal bleeding (IRR 1.13, 95% CI 0.76–1.69; NNH 3170). There was a borderline non-significant reduction of all-cause death (IRR 0.92, 95% CI 0.80- 1.01; NNT 821), and stroke (IRR 0.73, 95% CI 0.53–1.01; NNT 315) favouring DPI (Figures 1 and 2). At subgroup analyses a DPI strategy with the use of VLD dose of DOAC (i.e. rivaroxaban 2.5 mg twice daily) mitigated the risk of bleeding without any trade-off in efficacy compared to LD of DOAC regimens and a meta-regression analysis showed a significant interaction between dual antiplatelet therapy use and the risk of major bleeding, intracranial hemorrhage and stroke. Conclusions: In patients with CVD, the use of a LD of a DOAC in combination with antiplatelet therapy as part of a DPI regimen is effective in reducing ischemic events, at the expense of increased major and all bleeding but no increase of intracranial hemorrhage and fatal bleeding. A DPI strategy can be particularly advantageous with the use of a VLD of DOAC (i.e. rivaroxaban 2.5 mg twice daily) combined with a single antiplatelet agent among patients at high ischemic and low bleeding risk. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): D.C. declares that he has received consulting and speaker fees from AstraZeneca, Bayer, Boehringer Ingelheim, Daiichi Sankyo, outside the present work. F.C declares that he has received consulting and speaker fees from Biotronic, Amgen, Astra Zeneca, Servier, Menarini, BMS, outside the present work. F.A. declares that she has received consulting and speaker fees from Amgen, Bayer, BMS-Pfizer and Daiichi Sankyo, outside the present work. D.J.A. declares that he has received consulting fees or honoraria from Abbott, Amgen, Aralez, AstraZeneca, Bayer, Biosensors, Boehringer Ingelheim, Bristol-Myers Squibb, Chiesi, Daiichi-Sankyo, Eli Lilly, Haemonetics, Janssen, Merck, PhaseBio, PLx Pharma, Pfizer, Sanofi, and The Medicines Company and has received payments for participation in review activities from CeloNova and St Jude Medical, outside the present work. D.J.A. also declares that his institution has received research grants from Amgen, AstraZeneca, Bayer, Biosensors, CeloNova, CSL Behring, Daiichi-Sankyo, Eisai, Eli Lilly, Gilead, Janssen, Matsutani Chemical Industry Co., Merck, Novartis, Osprey Medical, Renal Guard Solutions and Scott R. MacKenzie Foundation. The remaining authors report no disclosures.